1998
DOI: 10.1016/s0009-9236(98)90036-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multiple doses of ritonavir on the pharmacokinetics of rifabutin*

Abstract: Ritonavir inhibited the metabolism of rifabutin and 25-O-desacetylrifabutin, suggesting that both are metabolized at least in part by CYP3A. Ritonavir may have enhanced rifabutin bioavailability by reducing either intestinal of hepatic metabolism of both. Clarithromycin is an alternative to rifabutin for antimycobacterial therapy that may be administered concurrently with ritonavir. Administration of ritonavir with a reduced rifabutin dosage regimen (150 mg every Monday, Wednesday, and Friday) is being investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 22 publications
8
42
0
1
Order By: Relevance
“…Ritonavir is a potent inhibitor of CYP3A and has been demonstrated that it can exacerbate the adverse reactions of rifabutin [13,14]. Subsequently, recent guidelines have proposed the use of intermittently administered rifabutin 150 mg 3 times per week or 150 mg daily with close monitoring of adverse effects when used in the combination with ritonavir.…”
Section: Discussionmentioning
confidence: 99%
“…Ritonavir is a potent inhibitor of CYP3A and has been demonstrated that it can exacerbate the adverse reactions of rifabutin [13,14]. Subsequently, recent guidelines have proposed the use of intermittently administered rifabutin 150 mg 3 times per week or 150 mg daily with close monitoring of adverse effects when used in the combination with ritonavir.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the consumption of grapefruit or grapefruit juice was not allowed from 2 weeks prior to the first dose and during the study, and the consumption of alcohol, caffeine, and xanthine-containing beverages was not allowed from 48 h prior to the first day of the study and throughout the study. Restriction of caffeine and xanthinecontaining beverages was required to isolate the adverse events caused by the potentially increased metabolism of caffeine, since ritonavir is not only an inducer of CYP3A but also an inducer of CYP1A2 (9).…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the anticipated increase in rifabutin exposure with concomitant saquinavir-ritonavir treatment, rifabutin was administered once every 3 days rather than daily in groups 1 and 2. Recruitment into group 3 was dependent on whether the group 2 regimen led to exposure of rifabutin or its active moiety (sum of rifabutin and its active metabolite, 25-Odesacetyl-rifabutin) that was within the established rifabutin area under the concentration-time curve from 0 to 24 h (AUC 0-24 ) range between 1.6 Ϯ 0.4 g ⅐ h/ml and 3.4 Ϯ 0.7 g ⅐ h/ml following daily administration of rifabutin at doses of 150 mg (9) or 300 mg (12), respectively. Thus, group 3, if required, was to be dosed either every second or every fourth day based on whether the observed deviations were higher or less than these established limits.…”
Section: Methodsmentioning
confidence: 99%
“…Co-administration of rifabutin with ritonavir increased area under the concentration-time curve (AUC) of rifabutin and its 25-O-desacetyl metabolite by four times and 35 times, compared with administration of rifabutin alone. 6 Patients receiving rifabutin and ritonavir without the reduction of dosages increased the risk of developing leucopenia, arthralgia, joint disorder, uveitis, and skin discoloration. 6,7 Because of the increased likelihood of rifabutin toxicities, the dosage of rifabutin should be reduced by at least 75% of usual dosage (300 mg once daily) or 150 mg 2-3 times a week when given with lopinavir/ritonavir.…”
Section: Commentmentioning
confidence: 99%
“…6 Patients receiving rifabutin and ritonavir without the reduction of dosages increased the risk of developing leucopenia, arthralgia, joint disorder, uveitis, and skin discoloration. 6,7 Because of the increased likelihood of rifabutin toxicities, the dosage of rifabutin should be reduced by at least 75% of usual dosage (300 mg once daily) or 150 mg 2-3 times a week when given with lopinavir/ritonavir. 8,9 To our knowledge, this is the first report of uveitis associated with concurrent administration of rifabutin and lopinavir/ritonavir.…”
Section: Commentmentioning
confidence: 99%